Safe long-term outcome after kidney donation in older donors: A single-center experience - Schuster, Antonia; Franke, Paula; Steines, Louisa; Zecher, Daniel; Hackl, Christina; Werner, Jens; Bergler, Tobias; Banas, Bernhard (Annals of Transplantation, 2020)
Background:Declining numbers of deceased donors and prolonged waiting time emphasize the importance of living kidney donation. Furthermore, because of the changing age structures with increasingly older recipients, the question of acceptance of older donors is becoming more relevant. However, sufficient long-term outcome data, espe-cially for older donors – including histopathological analysis – are lacking. The aim of this study was to analyze the Regensburg Living Donor Cohort with regard to age <65 and ³65 years, with a 10-year follow-up to iden-tify attributable risk factors.Material/Methods:All donors were analyzed for renal, cardiovascular, and pre-existing conditions at baseline and at follow-up. They were studied for predefined renal and additional end-points, eg cardiovascular ones and various stratifi-cations such as estimated glomerular filtration rate (eGFR). Additionally, as a unique feature in such an analy-sis, a histopathological workup of pre-existing chronic lesions of the donated kidneys was added. Results:On average, donors in the group <65 years were 50 years old at the time of donation compared with 68 years in the older group. Creatinine at baseline was 0.8 mg/dl in both groups, corresponding to an eGFR of 96.8±12.8 ml/min (Chronic Kidney Disease Epidemiology Collaboration [CKD-EPI]) and 83.7±10.3 ml/min (CKD-EPI). In the follow-up, donors ³65 years showed a statistically significantly worse eGFR and a greater eGFR decline, being accompanied by more pronounced chronic histopathological lesions, egglomerulopathy, than the con-trol group. However, this was largely constant over the entire observation period and no donor developed an end-stage renal disease or an eGFR below 30 ml/min.Conclusions:To summarize, living kidney donation after an intensive screening is safe even for older donors; however, a pre-cise aftercare to ensure balanced risk profile for living donors is mandatory.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Age Factors; Albuminuria; Pathology; Renal Insufficiency; Chronic; Tissue and Organ Procurement